120th' Anniversary of Lesgaft National State University of Physical Education, Sport and Health (Interview with the Rector S.E. Bakulev) - Sergey E. Bakulev (Высшее образование в России)
In his interview the Rector of Lesgaft National State University of Physical Education, Sport and Health highlights the milestones of 120-year history of this renowned higher education institution. The year ofUniversity foundation is the year of the start of the first modern Olympic games, and this fact accentuates the University contribution to the Olympic movement. The founder of the University is Petr Lesgaft - the famous scientist, physician and pedagogue, whose system of physical education became the basis for physical culture development in Russia. Today Lesgaft University is the world acknowledged centre of sports science. Special attention in interview is paid to the investigation areas.